Structuring and Restructuring Sovereign Debt : The Role of a Bankruptcy Regime - Bolton, Patrick (IMF Working Papers; Working Paper, 2007)
In an environment characterized by weak contractual enforcement, sovereign lenders can enhance the likelihood of repayment by making their claims more difficult to restructure ex post. We show however, that competition for repayment among lenders may result in a sovereign debt that is excessively difficult to restructure in equilibrium. This inefficiency may be alleviated by a suitably designed bankruptcy regime that facilitates debt restructuring.